Economics of Liming Kansas Cropland: Owner-Operator and Landlord-Tenant Considerations - Warmann, Gerald W. (My University, 1995)
This publication provides information that individuals that utilize cropland should consider when liming land.
MF2137_1995_10
Keywords: MF2137; Economics; Crops; MF